Secretory Carcinoma of Minor Salivary Gland in Buccal Mucosa: A Case Report and Review of the Literature - Durga Paudel; Michiko Nishimura; Bhoj Raj Adhikari; Daichi Hiraki; Aya Onishi; Tetsuro Morikawa; Puja Neopane; Sarita Giri; Koki Yoshida; Jun Sato; Masayuki Ono; Yoshitaka Kamino; et al. (Case Reports in Pathology)
Secretory carcinoma (SC) of the salivary gland was recently added to the fourth edition of the World Health Organization classification of head and neck tumors. Some salivary tumors, including acinic cell carcinoma, have been reclassified as SC. Most of these tumors are located on the parotid gland with very few cases reported in the minor salivary glands of the buccal mucosa. Herein, we present a case of SC of buccal mucosa, which appeared clinically as a benign lesion in a 54-year-old Japanese female patient. Histopathologically, the tumor cells presented with an eosinophilic cytoplasm with microcytic structure along with eosinophilic secretory material and hemosiderin deposit. Immunohistochemical staining revealed strongly positive staining for S100, vimentin, and mammaglobin and negative staining for DOG-1. The tumor was finally diagnosed as secretory carcinoma of the buccal mucosa. We present a review of the medical literature of SC arising from minor salivary glands. We found only 15 cases of SC of buccal mucosa out of 63 cases of SC in the minor salivary glands. They showed good prognoses and only one case of SC in the buccal mucosa exhibited local recurrence and lymph node metastases.